"I prefer to build trust": Parenting approaches to nurturing their children's digital skills. (August 2022) - Savic, Milovan
Positioned as digital natives, children are assumed to be experts in using social media. Though they are quick in picking up technical social media features, their ability to fully comprehend online risks is often questioned, raising parental anxiety about their children's engagement with digital media. While academic research has attempted to identify and measure digital skills, little is known about how these skills are negotiated within the family. This article draws on a qualitative study looking at the ways families with pre-teens negotiate the use of social media. Data collection included home-based interviews with 15 families from Melbourne, Australia ( n  = 30). In each family, the eldest child (10 to 15 years old) and one of the parents were separately interviewed. Additionally, social media tours (a first-hand display of online practices) complemented interviews with children. This article discusses how confidence in children's abilities, as well as personal perceptions of the parent's digital capabilities, affects how the parent navigates their children's use of digital media, as well as their level of success in developing safe digital practices with their children. This article uncovers three dominant parental approaches that emerged across the sample: the watchdog, the chaperon, and the collaborator. Central to each of these are varying degrees of trust in a child's ability to engage in safe practices online.